A Potent, Selective and Cell‐Active Allosteric Inhibitor of Protein Arginine Methyltransferase 3 (PRMT3)1. (27th February 2015) - Kaniskan, H. Ümit; Szewczyk, Magdalena M.; Yu, Zhengtian; Eram, Mohammad S.; Yang, Xiaobao; Schmidt, Keith; Luo, Xiao; Dai, Miao; He, Feng; Zang, Irene; Lin, Ying; Kennedy, Steven; et al.
Abstract PRMT3 catalyzes the asymmetric dimethylation of arginine residues of various proteins. It is essential for maturation of ribosomes, may have a role in lipogenesis, and is implicated in several diseases. A potent, selective, and cell‐active PRMT3 inhibitor would be a valuable tool for further investigating PRMT3 biology. Here we report the discovery of the first PRMT3 chemical probe, SGC707, by structure‐based optimization of the allosteric PRMT3 inhibitors we reported previously, and thorough characterization of this probe in biochemical, biophysical, and cellular assays. SGC707 is a potent PRMT3 inhibitor (IC50=31±2 nM, KD=53±2 nM) with outstanding selectivity (selective against 31 other methyltransferases and more than 250 non‐epigenetic targets). The mechanism of action studies and crystal structure of the PRMT3‐SGC707 complex confirm the allosteric inhibition mode. Importantly, SGC707 engages PRMT3 and potently inhibits its methyltransferase activity in cells. It is also bioavailable and suitable for animal studies. This well‐characterized chemical probe is an excellent tool to further study the role of PRMT3 in health and disease.